Characterization of the conformational hotspots of the RNA-dependent RNA polymerase complex identifies a unique structural malleability of nsp8 - Gharui, Sowmomita; Sengupta, Durba; Das, Atanu (Journal of Physical Chemistry B, 2024)
Several antiviral therapeutic approaches have been targeted toward the RNA-dependent RNA polymerase (RdRp) complex that is involved in viral genome replication. In SARS-CoV-2, although the RdRp is a multiprotein complex, the focus has been on the ligand binding catalytic core (nonstructural protein nsp12), and not the multiprotein functional dynamics. In this study, we focus on the conformational ensembles of the RdRp complex and their modulation by the presence of RNA, performing comprehensive microsecond-scale atomistic simulations of the apo- and RNA-bound complex. We delineate the differential impact of RNA on the constituent proteins, such as conformational polymorphisms, dominant segment-specific fluctuations, and the switch in dynamical crosstalk within the complex. We distinguish dynamical signatures of nsp7, nsp8, and nsp12 in the apo-state that are reduced in the presence of the RNA and appear to ``prime'' the complex for activity. Importantly, we identify a unique structural malleability of the nsp8 protein with high conformational heterogeneity in the apo state, especially at three sites (Y71 for nsp8A, and D52 and A66 for nsp8B). Our work highlights the functional implications of the polymorphism of nsp8 structures and reveals possibilities for the development of allosteric inhibitors.